Reduced regional cerebral blood flow in patients with heart failure - Roy, Bhaswati; Woo, Mary A.; Wang, Danny J.J.; Fonarow, Gregg C.; Harper, Ronald M.; Kumar, Rajesh (European journal of heart failure, 2017)
Aims Heart failure (HF) patients show significant lateralized neural injury, accompanied by autonomic, mood and cognitive deficits. Both gray and white matter damage occurs and probably develops from altered cerebral blood flow (CBF), a consequence of impaired cardiac output. However, the distribution of regional CBF changes in HF patients is unknown, but is an issue in determining mechanisms of neural injury. Our aim was to compare regional CBF changes in HF with CBF in control subjects using non‐invasive pseudo‐continuous arterial spin labelling (ASL) procedures. Methods and results We collected pseudo‐continuous ASL data from 19 HF patients [mean age 55.5 ± 9.1 years; mean body mass index 27.7 ± 5.3 kg/m2; 13 male) and 29 control subjects (mean age 51.4 ± 5.3 years; mean body mass index 25.7 ± 3.6 kg/m2; 18 male), using a 3.0‐Tesla magnetic resonance imaging (MRI) scanner. Whole‐brain CBF maps were calculated, normalized to a common space, smoothed and compared between groups using ANCOVA (covariates; age, gender and gray matter volume). Reduced CBF appeared in multiple sites in HF patients in comparison with controls, with principally lateralized lower flow in temporal, parietal and occipital regions. Areas with decreased CBF included the bilateral prefrontal, frontal, temporal and occipital cortex, thalamus, cerebellum, corona radiate, corpus callosum, hippocampus and amygdala. Conclusions Heart failure patients showed lower, and largely lateralized, CBF in multiple autonomic, mood and cognitive regulatory sites. The reduced CBF is likely to contribute to the lateralized brain injury, leading to the autonomic and neuropsychological deficits found in the condition.